Analisis Pembelajaran Bilingual di Sekolah Dasar - Hidayatullah, Muchamad; Nadia, Isna Ahsanu; Firdaus, Firda; Rani, Amanda Dwi Setyo; Ardani, Faisal Bagus; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Bilingual learning is implemented in the teaching and learning process with the intention of improving the linguistic intelligence of learners and equipping them with bilingual skills. This study aims to analyze bilungual learning in elementary schools. In this study, a literature review research method was applied. The results of this study provide strong evidence that the implementation of bilingual learning has a positive impact on the development of language skills and cognitive aspects of students at various levels of education, especially elementary school. This program can run effectively if supported by trained teachers, learning strategies that are appropriate to the development age of students and a supportive learning environment.